2021
DOI: 10.1002/jmv.27204
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different storage conditions on COVID‐19 RT‐PCR results

Abstract: Highlights It is best to store COVID‐19 swab samples in VTM to get the most reliable PCR results. Positive COVID‐19 swab samples can be stored for at least 5 days at both room temperature and 4°C without loss of positivity. Samples with high viral loads with CTs below 25 can be stored at both room temperature and 4°C without loss of positivity for up to 12 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…In a study by Yilmaz et al. [ 10 ], storage of samples at room temperature or refrigerated conditions did not affect significantly the CT value for the first 3 days, however fourth day onwards in samples stored at room temperature the CT values started to increase. They reported that all positives had increase in their mean CT values at both the temperatures [ 10 ].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In a study by Yilmaz et al. [ 10 ], storage of samples at room temperature or refrigerated conditions did not affect significantly the CT value for the first 3 days, however fourth day onwards in samples stored at room temperature the CT values started to increase. They reported that all positives had increase in their mean CT values at both the temperatures [ 10 ].…”
Section: Discussionmentioning
confidence: 95%
“…In a study by Yilmaz et al. [ 10 ] majority of the samples stored at 4 ​°C had consistent CT values over 5 days, however CT values increased by 1–4 amplification cycles for most of the samples stored at room temperature over 5 days. In our study though the CT values increased at regular intervals over 5 days there was no significant difference between the increase of the CT values at room temperature or refrigerated conditions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There nevertheless remains a gap in defining the upper time limit of such storage, particularly with reference to SARS-CoV-2. Thus, there have been several studies evaluating SARS-CoV-2 PCR sample integrity over refrigerator and room temperatures, [5][6][7][8][9] we have not come across any published, publicly available, study or data with which we could perform a direct comparison of the results obtained in this study.…”
Section: Discussionmentioning
confidence: 99%
“…With reference to SARS-CoV-2 detection through PCR in respiratory specimens specifically, there are several studies aimed at evaluating sample integrity following short-term storage at room temperature and at refrigerator temperatures (2-8°C). [5][6][7][8][9] There is, however, a paucity of studies evaluating sample viability upon long-term storage at standard ultra-freezer temperatures (-70 to -80°C). Guidelines for the SARS-CoV-2 PCR kits used in this study also state that respiratory specimen stability at standard refrigerator and freezer temperatures has not been established.…”
Section: Introductionmentioning
confidence: 99%